COMPACTING AS A PROSPECTIVE TECHNOLOGY FOR OPTIMIZATION OF INDUSTRIAL PRODUCTION SOLID DOSAGE FORMS - Bohuslavskyi , Yevhenii; Voskoboinikova , Halyna; Goy , Andriy; Yushkevych , I.; Zelinska , O. (Collection of scientific papers «ΛΌГOΣ», 2023)
In the conditions of high competition in the market for the production of readymade medicinal forms, development of new recipes, pharmaceutical companies have to look for new solutions to optimize the production process, improve quality and reduce the cost of production [1; 2].